The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1128/mcb.01592-08
|View full text |Cite
|
Sign up to set email alerts
|

Novel Types of Ca2+ Release Channels Participate in the Secretory Cycle of Paramecium Cells

Abstract: A database search of the Paramecium genome reveals 34 genes related to Ca 2؉ -release channels of the inositol-1,4,5-trisphosphate (IP 3 ) or ryanodine receptor type (IP 3 R, RyR). Phylogenetic analyses show that these Ca 2؉ release channels (CRCs) can be subdivided into six groups (Paramecium tetraurelia CRC-I to CRC-VI), each one with features in part reminiscent of IP 3 Rs and RyRs. We characterize here the P. tetraurelia CRC-IV-1 gene family, whose relationship to IP 3 Rs and RyRs is restricted to their C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(126 citation statements)
references
References 107 publications
5
121
0
Order By: Relevance
“…Most recent computational analysis of the mammalian RyR also came to the conclusion of six transmembrane domains (Ramachandran et al, 2013), just as we have shown for the homologous molecule CRC-IV in P. tetraurelia Ladenburger et al, 2009). .…”
Section: Note Added In Proofsupporting
confidence: 60%
See 3 more Smart Citations
“…Most recent computational analysis of the mammalian RyR also came to the conclusion of six transmembrane domains (Ramachandran et al, 2013), just as we have shown for the homologous molecule CRC-IV in P. tetraurelia Ladenburger et al, 2009). .…”
Section: Note Added In Proofsupporting
confidence: 60%
“…By using the P. tetraurelia genomic database (Aury et al, 2006;Arnaiz et al, 2007), genomic sequences that are indicative of CRCs with characteristic domain structures have been identified (Ladenburger et al, 2006;Ladenburger et al, 2009;Ladenburger and Plattner, 2011) (Fig. 1).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…In this evolutionary context, ciliates like Tetrahymena and Paramecium represent unique cases. Besides the expansion of PI-PLC genes, which are likely to have nonredundant roles, at least in Tetrahymena (this study), they apparently express members of an expanded family of IP3R-related Ca 2ϩ channels, the functionality of which has been previously demonstrated, at least in Paramecium studies (27,28). Collectively, these findings imply that the regulation of Ca 2ϩ homeostasis via a PI-PLCIns(1,4,5)P 3 -IP3R axis is likely to be evolutionarily conserved and elaborated in ciliates; accordingly, future studies aimed at unraveling the role of Tetrahymena PLC1-PLC2 (and PRIP) may focus primarily on well-established Ca 2ϩ -regulated processes.…”
Section: Discussionsupporting
confidence: 61%